Assessing bus transit service from the perspective of elderly passengers in Harbin, China. Issue 10 (26th November 2019) - Yuan, Yalong; Yang, Min; Wu, Jingxian; Rasouli, Soora; Lei, Da
Abstract: With the rapid aging population, the number of elderly passengers using bus services for daily travel will increase. Thus, it is increasingly more important for bus companies to understand the specific service requirements and expectations of elderly passengers. However, we are not aware of any dedicated studies on service requirement and travel satisfaction of the elderly. As an inclusive society is considered a key aspect of sustainable development, guaranteeing travel satisfaction is a sine qua non for sustainable transportation. Therefore, this study develops a customer satisfaction index (CSI) for the elderly. Assuming that perceived service quality affects passenger satisfaction, a structural equation model (SEM) is estimated to derive the importance of 10 dimensions of perceived service quality: reliability, time schedule, route characteristics, ticketing, driver service, convenience, safety and security, cleanliness, comfort, and information services. Furthermore, the effect of satisfaction on loyalty and filing complaints against the service company is examined. SEM is developed using data from a bus passenger survey, administered in 2017 in Harbin, China. The results show while some service dimensions such as time schedule and reliability are less important to the elderly (possibly due to their less strict time constraints) other dimensions such as service and security, convenience and driver service are in need of improvement due to the fact that they are very important for the elderly but their perceived performance from the elderly's perspective is low.